Temporal and Spatial Correlation Analysis of Sudden Drought and Flood Changes During Tobacco Growth in Guizhou Province - PENG Gaohui; LIU Zhentao; WANG Chao; XU Chenhui; WU Lijuan; ZHANG Zezhong (Renmin Zhujiang)
According to the daily precipitation data of 18 meteorologicalstations in Guizhou Province from May to August, 1958 to 2012, this paper analyzesthe temporal and spatial evolution characteristics of sudden drought and floodchange in the growth period of tobacco in Guizhou Province by the methods oflong and short-period sudden drought and flood change index, association rulesand so on. The results show that: During tobacco growth period, sudden changein long-period is mainly from drought to flood, and decreased gradually from westto east, the annual change curve of LDFAI intensity decreased at the rate of0.109/(10a), and the extremely sudden drought and flood events tend to decrease;Sudden drought and flood change occurs frequently in short period, the numberof drought to flood and flood to drought events is equal from May to June, theflood to drought occurs mainly from June to July, and the drought to flood occursmainly from July to August, the number of strong drought to flood events isgreater than that of strong flood to drought events, but the intensity isdecreased; Except for the eastern region, other regions and cities have astrong linkage between drought to flood and flood to drought, especially thecities with confidence of 100% will go through sudden drought and flood changeat the same time, so they should take the same preventive measures in advance.Theanalysis results provide a favorable help for tobacco farmers in flood control anddrought relief.